(untitled) (Journal of Oriental Studies, 2016)
This article is about the spiritual and cultural values of Koreans in Kazakhstan. 2014 was the 150th anniversary of Koreans residing in CIS countries, in Kazakhstan the Koreans have been living for almost 80 years. For 150 years the Koreans of the CIS countries have created a variety of material and spiritual historical and cultural values (performing arts, traditional medicine, agriculture, oral traditions, identity, seasonal customs, rituals, entertainment, festivals, etc.). Spiritual historical and cultural values still preserved and multiply Koreans, but to a greater extent in the form of a mixing of cultures through interaction.